2022
DOI: 10.1210/clinem/dgac325
|View full text |Cite
|
Sign up to set email alerts
|

Somatic RET Indels in Sporadic Medullary Thyroid Cancer: Prevalence and Response to Selpercatinib

Abstract: Context Although the majority of RET alterations are single nucleotide variants (SNV), small deletions and/or insertions have been reported at variable prevalence. No information about the efficacy of RET specific inhibitors in patients harboring RET indels, has been provided. Objective To present an update on the prevalence of RET indels in MTC and describe the efficacy of selpercatinib in patients with advanced RET indels M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…The prognostic role of the RET deletions (including indels) has not been clearly proved due to the few available data. However, in a recent paper, Elisei R. et al observed that MTC harboring RET indels, show a more aggressive phenotype with a high prevalence of advanced cases at diagnosis (45).…”
Section: Ret In-frame Deletionsmentioning
confidence: 97%
See 3 more Smart Citations
“…The prognostic role of the RET deletions (including indels) has not been clearly proved due to the few available data. However, in a recent paper, Elisei R. et al observed that MTC harboring RET indels, show a more aggressive phenotype with a high prevalence of advanced cases at diagnosis (45).…”
Section: Ret In-frame Deletionsmentioning
confidence: 97%
“…However, in a recent paper, Elisei R. et al. observed that MTC harboring RET indels, show a more aggressive phenotype with a high prevalence of advanced cases at diagnosis ( 45 ).…”
Section: Ret Deletions In Cancersmentioning
confidence: 99%
See 2 more Smart Citations
“…Selpercatinib also showed good efficacy in studies using a Chinese population [ 13 ]. It has been suggested that other RET alterations with less frequency, such as indels which indicate complex alterations such as small deletions or insertions or both, can also be treated with selpercatnib [ 14 ].…”
Section: Introductionmentioning
confidence: 99%